Design of Fractional Conversion Ratio Switched Capacitor DC-DC Converters by Using Loop-Connected - Krit Smerpitak; Sawai Pongswatd; Teerawat Thepmanee; Kei Eguchi (My University, 2015)
A switched-capacitor (SC) DC-DC converter and its loop-connected structure are proposed in this paper. Unlike the conventional series-connected converter, the proposed converter using loop connected provides the output voltage expressed as a combination of multiplication and subtraction. Therefore, the proposed converter can realize various kinds of output voltages as well as circuit size fewer than the conventional converter. Concerning the simple example of the proposed converter, simulation program with SPICE simulations and theoretical analysis are performed to clarify characteristics. The results of SPICE simulations show the following results: (1) The proposed converter can achieve higher power efficiency than the series-parallel type block when the number of capacitors is less than three. (2) In the case of the 2x and 1/2x conversion, the circuit size of the proposed loop- connected converter is less than 80% of that of the conventional converter. (3) Handy theoretical formulas to estimate power efficiency are obtained by the theoretical analysis. The results of the theoretical analysis are in good agreement with the SPICE simulated results.
Keywords: Spice; Switched capacitor; Advanced DC-DC Converters